Cross-Talk Between m6A- and m5C-Related lncRNAs to Construct a Novel Signature and Predict the Immune Landscape of Colorectal Cancer Patients - Song, Wei; Ren, Jun; Xiang, Rensheng; Yuan, Wenzheng; Fu, Tao (Frontiers in Immunology, 2022)
Background: N6-methyladenosine (m6A) and 5-methylcytosine (m5C) can modify long non-coding RNAs (lncRNAs), thereby affecting tumorigenesis and tumor progression. However, there is a lack of knowledge regarding the potential roles and cross-talk of m6A- and 5mC-related lncRNAs in the tumor microenvironment (TME) and their effect on prognosis. Methods: We systematically evaluated the expression patterns of m6A- and 5mC-related lncRNAs in 1358 colorectal cancer (CRC) samples from four datasets. Consensus clustering was conducted to identify molecular subtypes of CRC, and the clinical significance, TME, tumor-infiltrating immune cells (TIICs), and immune checkpoints in the different molecular subtypes were analyzed. Finally, we established a m6A- and 5mC-related lncRNA signature and a prognostic nomogram. Results: We identified 141 m6A- and 5mC-related lncRNAs by co-expression analysis, among which 23 lncRNAs were significantly associated with the overall survival (OS) of CRC patients. Two distinct molecular subtypes (cluster A and cluster B) were identified, and these two distinct molecular subtypes could predict clinicopathological features, prognosis, TME stromal activity, TIICs, immune checkpoints. Next, a m6A- and m5C-related lncRNA signature for predicting OS was constructed, and its predictive capability in CRC patients was validated. We then constructed a highly accurate nomogram for improving the clinical applicability of the signature. Analyses of clinicopathological features, prognosis, TIICs, cancer stem cell (CSC), and drug response revealed significant differences between two risk groups. In addition, we found that patients with a low-risk score exhibited enhanced response to anti-PD-1/L1 immunotherapy. Functional enrichment analysis showed that these lncRNAs related to the high-risk group were involved in the development and progression of CRC. Conclusions: We conducted a comprehensive analysis of m6A- and 5mC-related lncRNAs in CRC and revealed their potential functions in predicting tumor-immune-stromal microenvironment, clinicopathological features, and prognosis, and determined their role in immunotherapy. These findings may improve our understanding of the cross-talk between m6A- and m5C-related lncRNAs in CRC and pave a new road for prognosis assessment and more effective immunotherapy strategies.